Effects of a mastery intervention programme on the motivational climate and achievement goals in sport coaching: A pilot study - Haji Hassan, M. F.; Morgan, K. (International Journal of Sports Science and Coaching, 2015)
The task, authority, recognition, grouping, evaluation, and time structures (TARGET) have been identified as influential in determining a mastery motivational climate. To date, there is relatively little research on the use of TARGET based interventions in the sport setting. The purpose of this study was to examine the effects of a mastery intervention programme on sport coaches` TARGET behaviours and athlete`s perceptions of the motivational climate and achievement goal orientations. Study participants included four coaches and 43 of their athletes from a young adult sport population, representing a range of different sports. A multi-methods approach was used in the examination of the link between coaching behaviours and athletes` psychosocial responses. Coaches` behaviours were assessed at three time points (pre, mid, and post-intervention), and athletes` self-perceptions were measured at two time points (pre and post-intervention). For coach observations, the percentage `mastery`, `ego` and `neither` TARGET behaviours were calculated for each of the three filmed coaching sessions. Wilcoxon tests were conducted in order to measure the differences between athletes` pre- and post-intervention perceptions of the motivational climate, and goal orientations. Results revealed increased mastery coaching behaviours and significant increases in athlete`s perceptions of a mastery climate and task goal orientations and a significant decrease in ego perceptions of the climate and ego goal orientations. Given the adaptive motivational responses that are associated with a mastery climate and mastery goal orientations, this intervention has important implications for sport coaching.